01 A Reflection on Organizational Culture in Higher Education - Nadia Laura SERDENCIUC (International Journal of Social and Educational Innovation, 2019)
The present study focuses on the role of the organizational culture in sharing values, shaping goals and guiding actions of the organization’s members. It also discusses the relationship between the tangible components and the less visible ones in the structure of the organizational culture. After a brief description of a few coordinates defining the organizational culture, our study focuses on the context and on the descriptors that establish some traits of the specificity of the organizational culture in the contemporary higher education.